he cholera outbreak getting - back to the basics? - Abd Razak, Dzulkifli (1996)
FOODRELATED POISONING CAN BE described as a chain of events. It normally starts from a single source and tends to spread via the methods of food production, preparation, storage, distribution and lastly, consumption. Perhaps the recent cholera panic is a case in point, coming allegedly from ice suppliers spreading eventually throughout the state of Penang, and finally the whole nation. In every one of this situation, the challenge is to break out of the chain of events. This is easier said than done because the nature and incidence of poisoning can also be influenced by agricultural practices, food technology in industry and at home, as well as other ecological, environmental, socioeconomic and cultural practices.